Mesenchymal stromal cell derived extracellular vesicles as a therapeutic tool: immune regulation, MSC priming, and applications to SLE - Wong, Christophe; Stoilova, Ivana; Gazeau, Florence; Herbeuval, Jean-Philippe; Fourniols, Thibaut (Frontiers in Immunology, 2024)
Systemic lupus erythematosus is a chronic autoimmune disease characterized by a dysfunction of the immune system. Mesenchymal stromal cell (MSCs) derived extracellular vesicles (EVs) are nanometer-sized particles carrying a diverse range of bioactive molecules, such as proteins, miRNAs, and lipids. Despite the methodological disparities, recent works on MSC-EVs have highlighted their broad immunosuppressive effect, thus driving forwards the potential of MSC-EVs in the treatment of chronic diseases. Nonetheless, their mechanism of action is still unclear, and better understanding is needed for clinical application. Therefore, we describe in this review the diverse range of bioactive molecules mediating their immunomodulatory effect, the techniques and possibilities for enhancing their immune activity, and finally the potential application to SLE